Pengaruh Audit Fee, Rotasi Audit dan Ukuran Perusahaan terhadap Kualitas Audit : (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Financials yang Terdaftar di BEI Tahun 2020-2023) - Dina Erliana; Beti Nurbaiti; Endah Prawesti Ningrum; Tutty Nuryati; Tri Yulaeli (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This research aims to determine the influence of audit fees, audit rotation and company size on audit quality. The population used in this research is financial sector manufacturing companies listed on the Indonesia Stock Exchange 2020-2023. The sample in this research was 272 from 69 companies using a purposive sampling technique. The data collection method uses criteria that have been pioneered in this research with data analysis techniques using descriptive analysis tests, binomial logistic regression analysis tests and hypothesis testing. The results of this research show (1) Audit fees have a positive effect on audit quality, (2) Audit rotation has no effect on audit quality, (3) Company size has a negative effect on audit quality.